Effects of Mindfulness and Holotropic Breathwork on the Rehabilitation of Adolescents Who Use Psychoactive Substances: A Pilot Study (2023)
This pilot study aims to compare the effects of mindfulness and holotropic breathwork treatments on adolescents in the rehabilitation process for psychoactive substance use. Participants comprised 18 female adolescents aged 15–18 admitted to the Fundación Grupo de Apoyo, affiliated with the Colombian Family Welfare Institute. The Fundación is dedicated to rehabilitation from, detoxification from, and prevention of psychoactive substance use. The study utilizes a mixed methods approach with an exploratory design. Heart rate is used as an important indicator of psychological well-being and overall cardiovascular health, and the mean pretest/posttest heart rates of the control and experimental groups are compared quantitatively. The effects of both treatments on the study population are described qualitatively. The results show a reduction in heart rate in the mindfulness group compared to the control. The narratives of the participants and the institution’s workers show positive changes in emotional regulation and coping, better communication, and a reduction in stress and anxiety or the desire to use, as a result of both experimental treatments.